Pengaruh Bukaan (U-Turn) di Ruas Jalan Z.A. Pagar Alam Terhadap Kinerja Lalu Lintas (Studi Kasus U-Turn di Depan Wisma Bandar Lampung) - Gultom, Bona; Sulistyorini, Rahayu; Putra, Sasana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
Development of population in Bandar Lampung City and the demand for vehicles from year to year was increasing, such as private vehicles, public transportation, buses and others. This had an impact on the development of facilities and infrastructure of transportation which facilitated the movement occurring on the Zainal Abidin Pagar Alam road section. One of the facilities found on Z.A Pagar Alam road is the Median Opening (U-Turn) which changed direction by turning 180°. One of the effects of the U-Turn movement was going slowly or stopping vehicles. This would affect the movement of other vehicles on the main road. In addition, there were also many cases where the vehicle couldn’t rotate directly because of less radius of rotation. The purpose of this study was to determine the effect of the Median Opening (U-Turn) on the traffic performance at Z.A Pagar Alam road with the Gap Acceptance Method. The use of the Gap Acceptance Method would get the Queue Length value, Gap value and Wait Time (Follow Up Time). Based on the analysis and calculations carried out at the Median Opening (U-Turn) in front of Wisma Bandar Lampung, it could be concluded that the effect of the U-Turn on Monday morning from Tanjung Karang to Rajabasa and vice versa was the biggest effect on traffic performance where the gap was 439 vehicles and queue due to a gap was 899 vehicles, follow-up times was 309 vehicles and queue due to follow-up time was 1449 vehicles. Keywords : U-Turn, Gap Acceptance, Follow Up Time, Vehicle Queue